Pengaruh Nisbah Dan Suhu Pencampuran Selulosa Dan Pati Terhadap Sifat Dan Morfologi Bioplastik Berbahan Dasar Pati Umbi Talas - Wira Bima Stevent Sembiring; Irdoni HS; Bahruddin Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The use of plastic in large quantities impact on environment pollution as the effect of the plastic cesspool accumulation which cannot be decomposed naturally (non-biodegradable). Research bioplastics (biodegradable plastic) based starch done to find alternative to reduce the consumption of conventional plastics. But, the starch has a weakness on mechanical properties. The purpose of this study was to knowing the characteristics of taro starch and cellulose from banana stems, knowing the effect of water ratio, temperature and composition of the cellulose filler on mechanical properties and morphology of the bioplastics products. Manufacture of bioplastics made by the casting method, ie mixing taro tuber starch, glycerol, and cellulose. Bioplastics produced do some analysis, which includes the analysis of the chemical composition, tensile strength (tensile strenght), elongation (elongation at break), water uptake, biodegradation, SEM (Scanning Electron Microscopy) and analyzed using Response Surface Methodology (RSM). The most effected factor was significant to all the responds was the composition cellulose filler which followed by the temperature and water ratio. The best composition is bioplastic with filler cellulose 14,999%b/b, temperature 75,775oC and water rasio 20v/b which is tensile strenght was 6,906 MPa, elongation 10,906%, water uptake 28,491% and biodegradable 54,143%.Keyword : cellulose, glycerol, starch, tensile strength, and water uptake